2017
DOI: 10.1111/petr.12935
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic stem cell transplantation and acute kidney injury in children: A comprehensive review

Abstract: AKI in the setting of HSCT is commonly investigated among adult patients. In the same way, malignancies requiring treatment with HSCT are not limited to the adult patient population, AKI following HSCT is frequently encountered within pediatric patient populations. However, inadequate information regarding epidemiology and pathophysiology specific to pediatric patients prevents development of appropriate and successful therapeutic strategies for those afflicted. Addressing AKI in the context of sinusoidal obst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 84 publications
1
23
0
4
Order By: Relevance
“…Many post-transplant events such as lung toxicity, sepsis, cardiac involvement, admission to an intensive care unit, SOS, and acute GVHD are previously described risk factors for renal events in various pediatric and adult studies [1,2,24]. Among them, SOS is a repeatedly described risk factor [16,17,26,[30][31][32].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Many post-transplant events such as lung toxicity, sepsis, cardiac involvement, admission to an intensive care unit, SOS, and acute GVHD are previously described risk factors for renal events in various pediatric and adult studies [1,2,24]. Among them, SOS is a repeatedly described risk factor [16,17,26,[30][31][32].…”
Section: Discussionmentioning
confidence: 97%
“…Acute kidney injury (AKI) is a well-described complication after hematopoietic cell transplantation (HCT), affecting 20% to 84% of transplant recipients [1][2][3][4]. HCT is a multistep process including many treatments that can cause renal insults, such as conditioning regimens composed of intensive chemotherapy or radiation, nephrotoxic immunosuppressive agents, and prophylactic or therapeutic anti-infectious agents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, acute kidney injury (AKI) has become one of the major challenges, as it is an independent predictive factor for patient survival and progression to chronic kidney disease (CKD). 1,2 Although there are many reviews on HSCT, few of them concern the pediatric population, [3][4][5] and none of them concentrate on the nephrological aspects of HSCT.…”
Section: Current Methods Of Assessing Kidney Function Following Hematmentioning
confidence: 99%
“…HSCT can generate sustained damage to a variety of organs in children undergoing the procedure. Cardiac, renal, and pulmonary damage have been well described in pediatric HSCT recipients [6][7][8][9]. Previous studies have shown that children undergoing HSCT can also experience various impairments that can impact school performance [10,11].…”
Section: Introductionmentioning
confidence: 99%